Penerapan Doktrin Misbruik Van Omstandigheiden terhadap Pembatalan Akta Notaris Berdasarkan Putusan Pengadilan - Latifa Mustafida (Lex Renaissance, 2017)
AbstractThe problem in this research is how the development of the Doctrine of Abuse of state (Misbruik Van Omstandigheiden), particularly in the jurisdiction of the District Court of the city of Yogyakarta to  the authentic deed of Notary, as well as analyzing the legal consequences of the Court's decision on the revocation of the deed on the basis of the doctrine of abuse situation against a Notary and the penghadap party. This type of research used juridical empirical. The study concluded that the doctrine of abuse of court decisions by state (Misbruik Van Omstandigheiden) largely resulted in an authentic deed is canceled, the verdict there was a trend shift in principle proof of formal properties of the material truth in the proceedings. Therefore Notaries in the whole procedure and authentic act of making not only have to pay attention to the formal requirements, but it is necessary to examine the material truth of the deed that will be made, so as to prevent the occurrence of litigation or cancellation of the certificate of authentic products.Keywords: Abuse of state, Misbruik Van Omstandigheiden, contract, shift Proof.